Analisis Anteseden Financial Behavior Pada Mahasiswa Gen Z Prodi Akuntansi Universitas Muhammadiyah Surabaya - MSA, Gita Desipradani S.Pd MM; Fitriyah, Kurnia Lailatul; Surahman, Dedy (SUSTAINABLE, 2024)
This research was conducted regarding the phenomenon of young people in Indonesia regarding poor behavior and financial literacy and the emergence of technology-based financial products and services. The purpose of this study was to determine the effect of Financial Literacy (X1) and Financial Technology (X2) on Financial Behavior (Y) in Gen Z Students of Accounting Study Program, University of Muhammadiyah Surabaya. The research approach used in this study is a quantitative approach using questionnaires in data collection. The population in this study were active students of the Accounting Study Program for the 2019-2022 academic year, University of Muhammadiyah Surabaya. The number of samples is 60 respondents. The data were processed using the IBM Statistics SPSS 25 program, based on the results of the t test conducted it can be seen that financial literacy (X1) has a positive and significant effect on financial behavior (Y) and financial technology (X2) has no significant effect on financial behavior (Y). Based on the results of the F test conducted, it can be seen that Financial Literacy (X1) and Financial Technology (X2) simultaneously have a positive and significant effect on the financial behavior variable in Gen Z Students of Accounting Study Program, University of Muhammadiyah